2018
DOI: 10.1111/anu.12688
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic target of rapamycin inhibition with rapamycin induces autophagy and correlative regulation in white shrimp (Litopenaeus vannamei)

Abstract: Mechanistic target of rapamycin (mTOR) is a central regulator of cell growth and metabolism including autophagy. The mTORC1 signalling pathway is a major regulator of autophagy in response to nutrient levels. The drug rapamycin induces autophagy in various cell types and species by specifically inhibiting the activity of mTOR. To identify the genes and correlative regulatory pathways involved in cell metabolism and autophagy of Litopenaeus vannamei, we analysed the transcriptome of shrimps treated with rapamyc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 67 publications
0
6
0
Order By: Relevance
“…The IGF-I and TOR levels have been evaluated to correlate with growth in different aquatic animals, such as European sea bass (Dicentrarchus labrax) (Carnevali et al, 2006), tilapia (O. niloticus) (Yan et al, 2013), juvenile turbot (S. maximus) (Wang et al, 2016), and pacific white shrimp (Liu et al, 2018). In this study, it was observed that hybrid grouper fed with different levels of HFP obtained a significantly higher total crude protein level compared to the control.…”
Section: Discussionmentioning
confidence: 88%
“…The IGF-I and TOR levels have been evaluated to correlate with growth in different aquatic animals, such as European sea bass (Dicentrarchus labrax) (Carnevali et al, 2006), tilapia (O. niloticus) (Yan et al, 2013), juvenile turbot (S. maximus) (Wang et al, 2016), and pacific white shrimp (Liu et al, 2018). In this study, it was observed that hybrid grouper fed with different levels of HFP obtained a significantly higher total crude protein level compared to the control.…”
Section: Discussionmentioning
confidence: 88%
“…Mechanistic target of rapamycin (mTOR) represents a critical regulatory protein involved in protein production, cell growth/proliferation, autophagy, lysosomal function and metabolic pathways, and is considered a central regulator of cell growth 23 . It is admitted that mTOR is a primary suppressor of autophagy, which acts by controlling essential effectors at the transcriptional and post-transcriptional levels, and by directly phosphorylating the autophagy machinery 24 .…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, it has also been found that sustained molting steroid production and secretion in the molting glands of blackback land crab (Gecarcinus Lateralis) [17] and green crab (Carcinus maenas) [18] relied on mTOR-dependent protein synthesis [19]. In Litopenaeus vannamei, the inhibitor rapamycin inhibited the mTOR signaling pathway, significantly changed the expression of many autophagy-related genes, and significantly increased the ratio of LC3II/LC3I [20]. In Crassostrea gigas, 35 autophagy-associated proteins were first identified, followed by analysis of the expression and localization of microtubule-associated proteins 1A/1B-light chain 3 (LC3) and mTOR in different tissues of oysters [21].…”
Section: Introductionmentioning
confidence: 99%